Characterization of the novel HLA‐A*11:324 allele by sequencing‐based typing. (15th May 2019) - Cargou, Marine; Elsermans, Vincent; Top, Isabelle; Guidicelli, Gwendaline; Visentin, Jonathan
Abstract : HLA‐A*11:324 differs from HLA‐A*11:01:01:01 by one nucleotide substitution in codon 317 in exon 6.